The effect of enzymatic processing on banana juice and wine - Byarugaba-Bazirake, George William (Stellenbosch : Stellenbosch University, 2008)
Thesis (PhD (Viticulture and Oenology. Wine Biotechnology))--Stellenbosch University, 2008.